Light-induced secretion and transformation of neurotransmitter dopamine - Wei, Shuanghong; Liu, Chang; Wu, Zuomeng; Si, Jianmin; Huo, Xingxing; Shen, Cailiang; Zhen, Yi; Liu, Dongwei; Chen, Lei (Frontiers in Photonics, 2025)
Dopamine (DA) is one of the most important neurotransmitters in the human body, which is becoming a key breakthrough for addressing myopia, neurodegenerative diseases such as Parkinson’s disease and Alzheimer’s disease, and mental diseases such as depression and schizophrenia. However, the activity of DA shows diurnal and seasonal variations, which may be due to the influence of solar activity time on the biological clock of the suprachiasmatic nucleus. By irradiating ARPE-19 cells with red and near-infrared light of different wavelengths, we studied and confirmed that the secretion and transformation of the light-induced neurotransmitter DA significantly depend on light wavelength and light dose. LED-chip light sources with emission peaks at 620, 680, 730, 800, and 850 nm and phosphor-converted LED light sources with emission peaks at 710 and 830 nm were used. It was confirmed that both the red and near-infrared light with variant wavelengths and doses can induce DA secretion to some extent. Yet, the concentrations of DA induced by the wideband spectral light of W710 and SW830 are higher than those induced by the narrowband single-LED-chip light and remain relatively stable under variant light doses. Among all the light sources, the model SW830 light source is the best one. This paper proposes a noninvasive way to induce the secretion of neurotransmitter DA and paves a reliable way to treat myopia, neurodegenerative diseases, and other diseases by using the neurotransmitter DA and the basic knowledge of photophysiology.